Análise de estratégias de execução para edifícios verticais com diferentes sistemas construtivos - Barbosa, Maysa Fontoura (2005)
The civil construction management has been taken more attention of civil construction companies in aim alternatives to enhancing theirs management process, main that work with building construction because the growing competition and the exigency of their invest. In this set, the strategic planning is fundamental for the development and success of business because generates data that will guide the balance between the production planning expectation and the necessary costs for concluding a project. The supply of planning data and performances of building construction is get to divide of the simulation of the production strategy. The planning production represents the strategies because its products are some information: schedules, graphs and reports to arrive the execution efficiency. This research presents analyze the conduct of two different construction systems variables of three construction strategies. The construction systems studied were traditional construction system and the external walls in reinforced concrete construction system. The production strategies simulated concentrated in analyse only the tower and were without inversion of services; with partial inversion of services; and with total inversion of services. Like product of this research to claim develop a systematization to value and choose the production strategies to attend by the tall building construction companies.